Quinta Bienal de La Habana : Arte Sociedad Reflexion. - Araeen, Rasheed; Camara, Ery; Canclini, Néstor Garcia; González-Mora, Magda I.; Hernández, Ibis; Herrera Ysla, Nelson; Llanes, Llilian; Molina, Juan Antonio; Prieto, Margarita Sanchez; Rodriguez, Hilda Maria; Stellwag, Carla; Valdés Figueroa, Eugenio; et al. (La Habana : Quinta Bienal de La Habana, 1994)
Abad, Pacita ; Agri-Culturel, Groupe ; Aguessi-Vognon, Pierre ; Aguilera, Carlos René ; Aguirre, Carlos ; Akyem, Ras ; Alet, Thierry ; Alexander, Jane ; Alvarez, Pedro ; Araeen, Rasheed ; Arias, Fernando ; Arrechea, Alexandre ; Astorga, Leda ; Atkinson, Karen ; Avsar, Vahap ; Baltar, Brigida ; Banc, Mo ; Baroni, Rafaela ; Barrao ; Barroso, Abel ; Bazan, Sergio ; Becerra, Milton ; Ben-Thi, Jack ; Benaim, Ricardo ; Benski, Kuki ; Bereal, Ed ; Bessquet, Norma ; Bester, Willie ; Bickle, Berry ; Binder, Pat ; Blanco, Miguel Rio ; Boonma, Montien ; Borges, José Francisco ; Botero, Germán ; Boullosa, Marcelo ; Breleur, Ernest ; Brey, Ricardo ; Bruguera, Tania ; Burnside, Stanley ; Canas, Germán Martinez ; Capelán, Carlos ; Cardillo, Rimer ; Cardoso, Maria Fernanda ; Castillo, Marco ; Castillo, Mónica ; Catherine, Norman ; Cauduro, Rafael ; Centurión, Feliciano ; Cheifitz, Jann Peta ; Cheng, Carl ; Ching, Mel ; Chong, Albert ; Christanto, Dadang ; Cipis, Marcelo ; Coleman, Johhny ; Cookhorne, Robert ; Cruise, Wilma ; Crump, Alan ; Cruz-Villegas, Abraham ; Cuevas, Alonso ; Cuevas, Gonzalo Diaz ; Cuizon, Noel ; Cunha, Chico ; Damast, Elba ; Danay, Richard Glazer ; Daou, Annabel ; Davis, Annalee ; Deghati, Mancocher A. ; Deghati, Reza ; Dietzsche, Duna ; Dragotta, Susana ; Echeverri, Andrea ; Efrat, Benni ; Ehrenberg, Felipe ; Errázuriz, Paz ; Escobedo, Helen ; Etoundi Essamba, Angèle ; Facundo, Rodrigo ; Faria, Francisco ; Fernandes, Fátima ; Fernández, Antonio Eligio ; Ferrari, León ; Fortuny, Hugo ; Freire, Jadir ; Freistav, Luis ; Fuentemayor, Héctor ; Fuertes, Rosana ; Garaicoa, Carlos ; Garcia, Eduardo Rubén ; Garrido, Nelson ; Garza, Javier de la ; Gasparini, Paolo ; Gbadegesin, Sangodare ; Geers, Peter Kendell ; Germond, Graeme ; Girón, Mónica ; etc.
biografie
Spaans
Quinta Bienal de La Habana, 05/1994
boek